Human activity recognition through wearable devices - Candinegara, Edwin (2017)
Human activity recognition technology has received increasing attention from researchers in the recent years. This technology has a wide range of possible applications such as healthcare, security, sports, etc. As such, many researchers have developed activity recognition systems using various types of devices such as specially made sensors, video surveillance, and smartphones for data collection. With the recent introduction of smartwatch, some researchers have started collecting sensory data using both smartphones and smartwatches due to their non-intrusive nature and high penetration rate.